SIGNIFICANCE RESEARCH OF DARVISH MOBILITY MODEL PARAMETERS FOR THE CHARGE TRANSPORT DESCRIPTION IN NANOSCALE MOSFETS - A. M. Borovik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Using the methodology of screening experiments the most significant parameters of the Darwish mobility model are identified. The possibility of optimizing the drift-diffusion model in order to achieve the adequacy of the simulation results of nanoscale MOS structures.